2014
DOI: 10.1111/aas.12416
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration and fluid volume kinetics before major open abdominal surgery

Abstract: The degree of dehydration before major surgery was modest as evidenced both by urine sampling and volume kinetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 19 publications
3
44
1
1
Order By: Relevance
“…Two previous studies of elderly hospital patients showed that fluid retention worsens outcome [19,20]. Pre-operative patients with concentrated urine eliminate Ringer's acetate more slowly [21], which supports the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…Two previous studies of elderly hospital patients showed that fluid retention worsens outcome [19,20]. Pre-operative patients with concentrated urine eliminate Ringer's acetate more slowly [21], which supports the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…At baseline, the FRI of one third reached 4.0, which implicates dehydration [4]. In a previous study, FRI was 2.8 before open abdominal surgery when the patients took oral fluid on demand up to two hours preoperatively [5]. A FRI of 2.8 was also found in our subgroup that was given 500 ml of Ringer´s lactate several hours prior to surgery.…”
Section: Discussionsupporting
confidence: 66%
“…However, accumulating evidence suggests that concentrated urine is of importance to health in hospital patients. Concentrated urine strongly affects how patients humans handle intravenous fluid [5,6] and is associated with a higher incidence of postoperative complications after hip fracture surgery [1] and higher mortality in acute geriatric care [7].…”
Section: Introductionmentioning
confidence: 99%
“…Renal water conservation in the form of a high fluid retention index (FRI) was common, despite taking precautions like minimum-delay surgery and preoperative fluid administration. Our patients had an average FRI of 4.0, which can be compared to 2.8 in patients awaiting elective abdominal surgery [8] and 2.7 in healthy volunteers just before and 3.55 after a 90-min recreational physical exercise [7]. The FRI did not decrease during the surgical procedure, although fluid administration was not restrictive (mean 2.2 L during the surgery).…”
Section: Discussionmentioning
confidence: 68%
“…The colours used have been assigned RGB codes [7]. One urine tube was used to measure albumin excretion (a sign of glomerular damage), as well as the concentration of metabolic waste products (which can be used to quantify the degree of dehydration-induced renal water conservation) [7,8].…”
Section: Methodsmentioning
confidence: 99%